Maltotriose is the inducer of the maltose regulon of Escherichia coli. - Raibaud, O (1987)
In a cell-free system programmed with a plasmid bearing a malP'-'lacZ gene fusion under the control of malPp, beta-galactosidase synthesis was strictly dependent on the presence of both the MalT activator protein and the inducer of the Escherichia coli maltose regulon. We show that, among all maltodextrins tested (from maltose to maltoheptaose), only maltotriose was able to induce beta-galactosidase synthesis. Likewise, in an in vitro transcription system, initiation of transcription at malPp required the presence of the MalT protein and maltotriose along with the RNA polymerase holoenzyme; neither maltose nor maltotetraose could substitute for maltotriose.